Answer:

**Answer:**

338 in

**Step-by-step explanation:**

If each of the measures shown is the measure from the vertex to the point of tangency, then that measure contributes twice to the perimeter (once for each leg from the vertex to a point of tangency).

2(22 in + 27 in + 22 in + 98 in) = 2(169 in) = **338 in**

The distance d of a particle moving in a straight line is given by d(t) = 2t3 + 5t – 2, where t is given in seconds and d is measured in meters. Find an expression for the instantaneous velocity v(t) of the particle at any given point in time.

Please Help!!In 2010, Martin paid $5,518.00 in Social Security tax. The SS tax rate was 6.2%. What was Martin's taxable income in 2010?

Charissa is eating out with friends, and it is her turn to pay the gratuity. The bill for the food is 26.50. If she plans to tip the 20%, what should she pay?

Can someone explain how to do it aswell please and thank you

Find the slope of the line that passes through the pair of points.(2,2) AND (-2,-2)

Please Help!!In 2010, Martin paid $5,518.00 in Social Security tax. The SS tax rate was 6.2%. What was Martin's taxable income in 2010?

Charissa is eating out with friends, and it is her turn to pay the gratuity. The bill for the food is 26.50. If she plans to tip the 20%, what should she pay?

Can someone explain how to do it aswell please and thank you

Find the slope of the line that passes through the pair of points.(2,2) AND (-2,-2)

The value of the **expression **(0.5)^4 is 0.0625.

In this expression, (0.5) raised to the power of 4 means that you multiply 0.5 by itself four times.

So, it would be calculated as 0.5 x 0.5 x 0.5 x 0.5, which equals 0.0625.

When you raise a number less than 1 to a positive exponent, like in this case, the result is a smaller number because you are repeatedly **dividing** the original number by itself, which makes it smaller each time.

In this case, 0.5 is divided by itself four times, resulting in a much smaller value, 0.0625.

To explain further, **exponentiation **represents repeated multiplication. When you raise a number to an exponent, you are essentially multiplying that number by itself the specified number of times.

In this case, (0.5)^4 means multiplying 0.5 by itself four times, leading to the value 0.0625.

This concept is fundamental in **mathematics **and is used in various applications, including calculating compound interest, population growth, and many scientific calculations where values change over time or with repetition.

for such more questions on **expression **

#SPJ2

**Answer:**

2

**Step-by-step explanation:**

0.5 is the same thing as 1/2 and half of 4 is 2

**Answer:**

In Geometry, we have several undefined terms: point, line and plane. From these three undefined terms, all other terms in Geometry can be defined. In Geometry, we define a point as a location and no size. ... And the third undefined term is the line.

**Step-by-step explanation:**

−5x−9y

5x−9y

=3

=−2

**Answer:**

-18y=1

**Step-by-step explanation:**

Did it on Khan Academy

Solve for X

-3x = 24

/-3 on both sides

x = -8

/-3 on both sides

x = -8

B. 12/37

C. 12/35

D. 35/37

**Answer:**

A

**Step-by-step explanation:**

Use the SOH CAH TOA

Tangent = Opposite / adjacent

tan (a) = 35 / 12

**Answer:**

the answer is obviously going to be a

hx = 5x + 2

Write the expressions for (g - h)(x) and (g * h)(x) and evaluate (g + h)(−2).

**Answer:**

**Step-by-step explanation:**

Given the functions g(x) = x − 3x and h(x) = 5x + 2, we are to calculatae for the expression;

a) (g - h)(x) an (g * h)(x)

(g - h)(x) = g(x) - h(x)

(g - h)(x) = x − 3x -(5x+2)

(g-h)(x) = x-3x-5x-2

**(g-h)(x) =-7x-2**

b) (g * h)(x) = g(x) * h(x)

(g * h)(x) = (x − 3x)(5x+2)

(g * h)(x) = 5x²+2x-15x²-6x

(g * h)(x) = 5x²-15x²+2x-6x

**(g * h)(x) = -10x²-4x**

c) To get (g + h)(−2), we need to first calculate (g + h)(x) as shown;

(g + h)(x) an (g * h)(x)

(g + h)(x) = g(x) +h(x)

(g + h)(x) = x − 3x + (5x+2)

(g+h)(x) = x-3x+5x+2

(g+h)(x) =3x+2

Substituting x = -2 into the resulting function;

(g+h)(-2) = 3(-2)+2

(g+h)(-2) = -6+2

**(g+h)(-2) = -4**